The Self-Identity Construction of Virtual Idol Hatsune Miku Young Adult Fans - Cempaka Harum, Alexandria (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2025)
This study examines the self-identity construction of young adult fans of the Japanese virtual idol Hatsune Miku using a qualitative cyber-phenomenology approach and Berger and Luckmann’s Social Construction of Reality theory. Data were collected through semi-structured in-depth interviews. Findings reveal that engagement with Hatsune Miku serves not only as entertainment but also as a source of emotional support, self-reflection, and affiliation within digital communities. Through processes of externalization, objectivation, and internalization, virtual interactions were found to shape a self-identity more closely connected to personal aspirations and social acceptance. All informants reported experiencing stigma linked to cultural stereotypes, such as being labeled wibu or “low nationalist,” which in turn fostered greater tolerance for cultural differences and acceptance of technological innovation. This study highlights the role of virtual idol engagement as a meaningful arena for identity formation and social adaptation in the digital era